Association between Healthy Lifestyle Factors and Metabolic Syndrome Risk: A Prospective Analysis of the Korean Genome and Epidemiology Study - Jialei Fu; Sangah Shin (Diabetes & Metabolism Journal, 2025)
Background To investigate the association of adherence to five modifiable lifestyle factors (limiting alcohol, physical activity, limiting smoking, favorable diet quality, and adequate sleep) with metabolic syndrome (MetS) risk in Korean adults. Methods Health Examinees Study data were used, and 41,368 participants aged 40 to 69 years were included. Cox proportional hazards regression analyses assessed the associations of individual and combined healthy lifestyle factors (32 and 16 lifestyle profiles in men and women. Results During a median 4.2-year follow-up, 6,213 participants were newly diagnosed with MetS. Adherence to more healthy lifestyle factors (4–5 vs. 0–1) could lower MetS risk by 28% and 12% in men and women (hazard ratio [HR], 0.72; 95% confidence interval [CI], 0.63 to 0.83 in men; HR, 0.88; 95% CI, 0.78 to 0.99 in women). Each additional healthy lifestyle could reduce the risk of MetS by 10% and 6% in men and women. The pooled analysis yielded similar results based on similar numbers of healthy lifestyle factors, the risk of MetS decreased as the number of healthy lifestyle factors increased. Conclusion Adherence to more healthy lifestyle factors was inversely associated with MetS risk. These findings highlight the importance of limiting drinking in managing MetS. Future research should consider the synergistic effects of emerging lifestyle factors, such as sleep duration, on chronic disease development, while focusing on the effects of traditional lifestyle factors.